Anatomical Characteristics of Genus Cassine (Celastraceae) Leaves - Muliyah, Evi; Yusniati, Euis; Hariri, Muhammad Rifqi; Zulkarnaen, Rizmoon Nurul (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
Cassine is a genus of plants belonging to the family Celastraceae. Species of Cassine are among those preserved through ex-situ conservation efforts at the Bogor Botanical Gardens. This study aims to provide a comprehensive overview of the anatomical characteristics of leaf stomata in four distinct Cassine species. Stomatal and epidermal observations were conducted using the replica method. The findings reveal that all Cassine species exhibit anisocytic stomata, characterized by a central guard cell surrounded by three neighboring cells of unequal size. Furthermore, stomata were confined to the abaxial (lower) surface of the leaf, with none present on the adaxial (upper) side. This distribution indicates that gas exchange in Cassine leaves primarily occurs on the lower surface, reflecting a significant physiological adaptation. These observations offer valuable insights into the structural and functional traits of Cassine species conserved at the Bogor Botanical Gardens. Karakteristik Anatomi Daun Genus Cassine (Celastraceae) ABSTRAK: Cassine adalah genus tanaman yang termasuk dalam keluarga Celastraceae. Tanaman Cassine merupakan salah satu spesies yang dilestarikan dalam konservasi ex-situ di Kebun Raya Bogor. Penelitian ini berfokus untuk memberikan gambaran yang komprehensif mengenai karakteristik anatomi stomata daun pada empat spesies Cassine yang berbeda. Pengamatan stomata dan epidermis diperoleh dengan menggunakan metode replika. Temuan penelitian mengungkapkan bahwa semua spesies Cassine menunjukkan stomata anisositik, yang ditunjukkan oleh sel penjaga pusat yang dikelilingi oleh tiga sel yang berdekatan dengan berbagai ukuran. Selain itu, stomata terbatas pada permukaan abaksial (bawah) daun, tanpa ada yang ada di sisi adaksial (atas). Hal ini menunjukkan bahwa pertukaran gas pada daun Cassine terutama terjadi di bagian bawah, yang mencerminkan adaptasi fisiologis yang penting. Pengamatan ini memberikan wawasan yang berharga tentang sifat struktural dan fungsional dari spesies Cassine yang disimpan di Kebun Raya Bogor.